APLIKASI PENGUKUR KELAYAKAN TEMPAT TINGGAL MENGGUNAKAN METODE NAIVE BAYES - Ivan Andrew Yoshua; Jeanny Pragantha; Tri Sutrisno (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
Application for measuring the feasibility of residence by using the Naive Bayes method is a method for measuring the feasibilty of a house. This method was created for PT. Ady Karya Raya Nusantara employees to replace the PT Ady Karya Raya method which still uses manual method. There are 2 programming languages used to make this application, namely PHP and Python. PHP for the user interface and python for the calculation. Testing was done by User Acceptence Testing (UAT) and count testing. UAT testing to check buttons and features and count testing to check whether the results of the manual method are the same as the Naive Bayes method. From the two tests conducted it can be seen that the Naive Bayes method can be applied to replace the manual method and also all buttons and features in the application function properly.